Revealing changes in molecular composition of plant cell walls on the micron-level by Raman mapping and vertex component analysis (VCA) - Gierlinger, Notburga (Frontiers in Plant Science, 2014)
At the molecular level the plant cell walls consist of a few nanometer thick semi-crystalline cellulose fibrils embedded in amorphous matrix polymers such as pectins, hemicelluloses and lignins. The arrangement of these molecules within the cell wall in different plant tissues, cells and cell wall layers is of crucial importance for a better understanding and thus optimized utilization of plant biomass. During the last years Confocal Raman microscopy evolved as a powerful method in plant science by revealing the different molecules in context with the microstructure. In this study two-dimensional spectral maps have been acquired of micro-cross-sections of spruce (softwood) and beech (hardwood). Raman images have been derived by using univariate (band integration, height ratios) and multivariate methods (vertex component analysis, VCA). While univariate analysis only visualizes changes in selected band heights or areas, VCA separates anatomical regions and cell wall layers with the most different molecular structures by projecting the data to the identified orthogonal subspace in an interactive way and finding the endmember by repeated iteration. Beside visualization of the distinguished regions and features the underlying molecular structure can be derived based on the endmember spectra. Only one pure component spectrum (lignin from the cell corner) was extracted, while all other endmember spectra represented mixtures characteristic for the different resolved spatial areas. VCA revealed that the lumen sided S3 layer has a similar molecular composition as the pit membrane, both revealing a clear change in lignin composition compared to all other cell wall regions. Within the S2 layer a lamellar structure was visualized, which was elucidated to derive also from slight changes in lignin composition and content and might be due to successive but not uniform lignification during growth.